1990
DOI: 10.1002/spe.4380200302
|View full text |Cite
|
Sign up to set email alerts
|

A system for adaptive disk rearrangement

Abstract: The speed of mass storage devices has a significant impact on the performance of computer systems. The speed that is realized on a particular mass storage device, however, depends heavily on how that device is used. Operating systems, such as the UNIX time‐sharing system, use layout policies and head‐scheduling disciplines that are designed to work well on average. Numerous studies have shown that disk access patterns exhibit a high degree of locality. Further, studies have shown that these access patterns do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…The following studies consider disk layout. The earliest studies of adaptive disk layout are theoretical ones [13] or those based on simulation [14]- [17]. Wong demonstrated that the organ-pipe method, which places the most frequently accessed data in the middle of the disk, was suitable for random disk accesses.…”
Section: Data Placement Controlmentioning
confidence: 99%
“…The following studies consider disk layout. The earliest studies of adaptive disk layout are theoretical ones [13] or those based on simulation [14]- [17]. Wong demonstrated that the organ-pipe method, which places the most frequently accessed data in the middle of the disk, was suitable for random disk accesses.…”
Section: Data Placement Controlmentioning
confidence: 99%
“…An example is to identify data items -blocks [1,3,43], cylinders [53], or files [48,49,54] -that are referenced frequently and to relocate them to be close together. Rearranging small pieces of data was found to be particularly advantageous [1] but in doing so, contiguous data that used to be accessed together could be split up.…”
Section: Background and Related Workmentioning
confidence: 99%
“…As discussed in Section 2, over the last two decades, there have been several attempts to improve spatial locality in storage systems by clustering together hot data [1,3,43,48,49,53,54]. We refer to these schemes collectively as heat clustering.…”
Section: Heat Clusteringmentioning
confidence: 99%
“…Finally, some work has been done on block replacement to improve I/O performance [18,19], but are not integrated in an autonomic system as ours.…”
Section: Related Workmentioning
confidence: 99%